Pengembangan Media Pembelajaran Bahasa Indonesia Berbasis Video Animasi pada Materi Teks Deskripsi Kelas VII MTs Swasta Darul Ulum Budi Agung - Fatimah Azzahra Dalimunthe; Tri Indah Kusumawati; Budiman Budiman (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study was conducted under the title “Development of Indonesian Language Learning Media Based on Animated Videos for Grade VII MTs Swasta Darul Ulum Budi Agung Descriptive Text Material,” which was motivated by low student motivation and understanding of descriptive text lessons. This situation occurred because attractive and interactive learning media were rarely used, causing students to tend to be passive in the learning process. The research methodology employed the Research and Development (R&D) method using the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation. The research population consisted of students at Darul Ulum Budi Agung Private Islamic Junior High School, with a sample size of 30 students in the experimental group and 30 students in the control group. Data collection was conducted using interviews, tests, and questionnaires. Validation was provided by experts in the fields of content, media, and language. This study shows that the use of educational media in the form of animated videos falls under the category of highly suitable for use, both in terms of content and presentation. This media is capable of enhancing students' learning motivation, clarifying their understanding of descriptive text concepts, and creating a more engaging and interactive learning environment. In other words, the use of animated videos can serve as an innovative solution as a learning medium for Indonesian language, particularly descriptive text material, to improve the quality of education at MTs Swasta Darul Ulum Budi Agung.